Adaptation and validation of the personality assessment questionnaire on 12 year old children in Sri Lanka - De Zoysa, P.; Rajapakse, L.; Newcombe, P.A. (My University, 2007)
The objective of this study was to adapt and validate the child version of the Personality Assessment Questionnaire with12-year-old Sinhala speaking school children in Sri Lanka. Content and consensual validity was determined by the Delphi Process. Criterion validity was determined by the degree of consensus between a clinical psychologist’s assessment and respondent’s total score on the instrument. Test-retest and internal consistency reliability were determined in two ways - a large group administration and a small group administration. The instrument showed satisfactory content and consensual validity. The cut-off score for the Sinhala version of the Child PAQ was determined as 89, at a sensitivity of 71.1% and specificity of 69.4% (95% confidence interval). The validated version’s full scale test-retest and internal consistency reliability were satisfactory. The instrument is best administered in small rather than in large groups of respondents.